THE INFLUENCE OF THE USE OF ICT ON LEARNING ACHIEVEMENT OF AQIDAH AHLAK - Mulyoto, M; Mujiburrohman, M; Subando, Joko (Proceeding of International Conference of Islamic Education, 2023)
The purpose of this study was to determine the effect of the use of ICT on learning achievement in Aqeedah Akhlak lessons. The method used is quantitative with a correlational approach. Data collection was carried out using observation techniques, documentation and questionnaires. The results showed that the use of ICT, learning motivation, and student learning outcomes at MI Muhammadiyah Walen 1 were in the sufficient category. Partially, the use of ICT has a significant effect on student learning outcomes of 0.236, included in the "moderate" category; Learning motivation has a significant effect on student learning outcomes of 0.314 included in the "high" category. Simultaneously the use of ICT and learning motivation have a significant effect on student learning outcomes of 0.198 included in the "medium" category. The results of this study are expected to provide benefits for education administrators, government, and society